Penguatan Kemampuan Teknis Desain Grafis Percetakan bagi Siswa SMK di Samudane, Kabupaten Lombok Tengah - Pribadi, Agus; Yunus, Muhammad; Rismayati, Ria (CV. Global Cendekia Inti, 2025)
Nowadays, most of SMK’s graduates in Central Lombok Regency are not yet ready to directly apply their skills and potential to work place. Multimedia expertise field of Graphic Design competency for Printing products is a favorite choice for prospective SMK’s students in Central Lombok Regency. Less than optimal learning is often experienced by SMK in remote areas, especially non-state schools; mostly due to limited learning devices. SMK in remote areas and private schools accommodate many students who cannot attend state schools which are generally located in the center city or other urban area. The field conditions that occur are the lack of graduate capacity to meet the needs of graduate users. Main problem faced by SMK is the lack of device support in learning and learning experience in practical derived from the world place. Implementation of the Community Service Program provides an answer to these needs. SMK Al Fajri as a partner becomes a accommodator for workshop activities to assist in increasing the capacity of students in preparing Graphic Design for Printing products. Students are given practical training and work on design projects as training to strengthen their technical skills. Communication and interaction exercises are added to complement students' competencies. Based on the evaluation, all workshop participants gained new experiences, increased technical and non-technical capacities. 80% of students can create Graphic Designs for Printing products independently and based on orders, without having to be given examples and direct guidance.